Penggunaan Strategi Tindak Tutur Direktif Menyuruh dalam Bahasa Minangkabau di Nagari Bukik Batabuah Kabupaten Agam - Yosi Amelia Putri; Siti Ainim Liusti (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
Language in the point of view of communication is seen as a tool for transmitting data from the brain of the speaker to the brain of the speech partner. However, the speech strategies used by speakers when transmitting such data are often not quite right, so the data is not accurate. This study aims to describe what speech strategies are used by the Nagari Bukik Batabuah people in the directive speech acts in Minangkabau language, as well as describe the nonlinguistic context contained in the speech. This research was conducted qualitatively using descriptive methods. The research data is in the form of speech that contains directive speech acts commanding in minangkabau language which are spoken directly. The data were collected by using uninvolved conversation observation method with recording and note-taking techniques. The results of the data analysis showed that the people of Nagari Bukik Batabuah often used a bald-on-record strategy as many as 107 data from 152 data. The cultural context contained in the utterance is influenced by (1) habits that have been passed down for generations by the people, (2) accustomed to something that has happened in ancient times, (3) accustomed to the dominant behavior of the people, and (4) because the culture is formed by itself. Meanwhile, the direct context of the speech is expressed in informal language, but still uses the ethics of speaking Kato Nan Ampek which is the procedure for speaking of Minang people. The topic of speech is not far from the daily life of the people. Also, the function or purpose of the speech act also tends to be clear, namely to tell the speech partner to do something. Through this research, readers can see what factors can help them in conveying their intentions accurately.